Drawing Representation in Design - Scutt, Sarah (Faculty of Art & Design, Monash University, 2006)
This paper reports work-in-progress for a research project involving 1st year Design students at Curtin University. This research examines if a computational environment supports multiple visual representations applicable to the idea generation process. The impetus to carry out this research began when Design eliminated the portfolio presentation and interview as part of its entry requirements and relied solely on the Tertiary Entrance Exam scores for the selection of its applicants. Experience has shown that student’s prior experiences and knowledge of visual communication has a significant influence on their approach, attitudes and perception of design. Students who have studied art at high school demonstrated a higher level of achievement and performance in their 1st year of study than those who did not. Traditionally, student designers have drawn initial design ideas with a pencil on paper and drawing has been seen to be a spontaneous and direct means to produce visual representations of ideas. However, these representations can be limited by the students skills and the media used. This paper investigates how a computational environment might support students with drawing skills and the idea generation processes. A symmetrical configuration task was given to two test groups, the first used traditional hand drawn methods, and the second used digital media. The results have implications for understanding drawing in Design.